Analysis of the physical structure of a food and nutrition unit in Picos, Piauí (Research, Society and Development, 2022)
Objective: To evaluate the hygienic-sanitary conditions of a Food and Nutrition Unit (UAN). Methodology: Cross-sectional, descriptive and quantitative study carried out in august 2021 at the UAN located in Picos-PI using the checklist of RDC nº 275 of October 21, 2002 from the Ministry of Health. Results: The compliance percentages of five topics were identified: 1) Buildings and installations with 79.74%, being considered the main problems in walls and ceilings; 2) Equipment, furniture and utensils with 100%, as it is a relevant point for preparing meals and functioning; 3) Handlers with 92.85%, identifying only the absence of hand washing posters; 4) Production and transportation of food with 66.66%, due to not carrying out labeling and transportation operations; 5) Documentation with 100% compliance. Conclusion: The analyzed UAN has a satisfactory hygienic-sanitary panorama and the checklist is a widely used tool, due to its degree of confidence and practicality.